2002
DOI: 10.1182/blood.v99.5.1638
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin prevents endotoxin-induced hypotension by inhibiting the induction of nitric oxide synthase in rats

Abstract: Antithrombin (AT) prevents Escherichia coli-induced hypotension in animal models of sepsis, and it further reduces the mortality of patients with septic shock. In the present study, we examined whether AT may prevent the endotoxin (ET)-induced hypotension by promoting the endothelial release of prostacyclin (PGI 2 ) in rats. Intravenous administration of AT (250 U/kg) prevented both hypotension and the increases in plasma levels of NO 2 ؊ / NO 3 ؊ in rats given ET. Lung expression of messenger RNA (mRNA) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…Consistent with this hypothesis, AT has been shown to inhibit pulmonary vascular injury and hypotension in rats challenged with lipopolysaccharide by inhibiting leukocyte activation through promotion of the endothelial release of PGI 2 . 11,12 In contrast to these reports, AT has been demonstrated to inhibit leukocyte activation directly. [13][14][15] These observations suggest that anti-inflammatory effects of AT may be mediated mainly by its direct inhibitory properties on leukocyte activation.…”
Section: Introductionmentioning
confidence: 85%
“…Consistent with this hypothesis, AT has been shown to inhibit pulmonary vascular injury and hypotension in rats challenged with lipopolysaccharide by inhibiting leukocyte activation through promotion of the endothelial release of PGI 2 . 11,12 In contrast to these reports, AT has been demonstrated to inhibit leukocyte activation directly. [13][14][15] These observations suggest that anti-inflammatory effects of AT may be mediated mainly by its direct inhibitory properties on leukocyte activation.…”
Section: Introductionmentioning
confidence: 85%
“…239 The enhanced production and release of prostacyclin (PGI), an anti-inflammatory signal, diminishes LPS-induced TNF-and inducible NOS in preventing LPS-induced hypotension. 240 Apart from suppressing P-selectin expression to inhibit leukocyte rolling, 241 ATIII deactivates neutrophil chemotaxis towards IL-8. 242 In vivo, AT III exhibits a wide range of anti-inflammatory effects on human sepsis.…”
Section: Anticoagulation Relevance To Anti-inflamationmentioning
confidence: 99%
“…The persistent NO production in septic patients may result from other unknown mediator(s) that are generated by LPS. The endogenous coagulation inhibitors reverse the vascular hyporeactivity induced by LPS (16,18). Protein C and ATIII have been studied extensively as the protective modulators of septic shock (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…ATIII inhibits nuclear factor-B (NF-B) activation in monocytes and endothelial cells (17). In addition, it has been shown that ATIII prevents LPS-induced hypotension by inhibiting NOS induction in animals (18).…”
mentioning
confidence: 99%